Challenges of online collaborative learning among special needs university students - Hidayu Shafie,; Ireena Nasiha Ibnu,; Noori, Abdullah; Nurhilleny Rosly,; Nadia Anuar,; Nur Husna Serip Mohamad, (Penerbit Universiti Kebangsaan Malaysia)
Teaching and learning in the 21st century is no longer confined in the four walls of a classroom, as classes can also be conducted online. However, a predominant disadvantage of online learning is the limited opportunity for students to have face to face interaction with educators and peers. In contrast to able-bodied students, online collaborative learning among special needs students (SNS) has not been closely examined and their experience has been minimally evidenced in the current body of literature. Therefore, the purpose of this study was to investigate challenges faced by the special needs university students when having online collaborative learning. This study was conducted quantitatively, whereby a survey method was used for the data collection. Analysis of data was performed using SPSS, specifically employing descriptive statistics analysis. Based on the findings of the study, it was found that the SNS in this study mostly had problems communicating with their peers during online collaborative learning. They were not really lacking in collaborative skills, but they were more concerned about their peers’ perspectives on their disabilities, and their abilities to do group work. In addition, they also did not have many issues with assistance tools and technology when doing online work with their peers. In conclusion, to ensure that SNS have a meaningful learning experience in collaborative learning, all parties should be made aware of and given exposure on working with SNS in all educational institutions in the online setting.